Ali : a Life - Eig, Jonathan (Boston : Houghton Mifflin Harcourt, 2017)
"Based on more than 500 interviews, including Muhammad Ali's closest associates, and enhanced by access to thousands of pages of newly released FBI records, this is a ... story of a man who became one of the great figures of the twentieth century [boxing world]"--
Includes bibliographical references and index.
Keywords: Ali, Muhammad, -- 1942-2016; Boxers (Sports) -- Biography -- United States; African American boxers -- Biography; Parkinson's disease -- Biography -- Patients -- United States; African Americans -- Social conditions -- 20th century; SPORTS & RECREATION / Boxing; BIOGRAPHY & AUTOBIOGRAPHY / Sports; RELIGION / Islam / General; United States -- Race relations -- 20th century; Biographies